2018
DOI: 10.1177/1098612x18762883
|View full text |Cite
|
Sign up to set email alerts
|

Detection of feline coronavirus mutations in paraffin-embedded tissues in cats with feline infectious peritonitis and controls

Abstract: Objectives The amino acid substitutions M1058L and S1060A in the spike protein of feline coronavirus (FCoV) have been postulated to be responsible for the development of the pathogenic feline infectious peritonitis virus (FIPV), which causes feline infectious peritonitis (FIP). The aim of the following study was to investigate the presence of mutated virus in tissue samples of cats with and without FIP. Methods The study population consisted of 64 cats, 34 of which were diagnosed with FIP and 30 control cats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…5 Later studies confirmed these findings and only detected few [25][26][27] or no FCoV at all with S1060A. 33 As such, M1058L is the more common S protein substitution, which is also reflected by the results of the present study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…5 Later studies confirmed these findings and only detected few [25][26][27] or no FCoV at all with S1060A. 33 As such, M1058L is the more common S protein substitution, which is also reflected by the results of the present study.…”
Section: Discussionsupporting
confidence: 85%
“…This has already been observed in other studies using the same method. 27,33 Another reason could be the absence of the particular S gene mutations examined here and the presence of other mutations involved in FIP pathogenesis inst ead. 6,8,9,14,15,38,39 Some other mutations, such as in the 3c gene, have been discussed as playing a role in FIP pathogenesis, but a clear causal relationship to FIP still has not been identified.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Spontaneous mutations of the S gene [6], ORF3abc [7,8], and ORF7ab [9,10] in the FCoV genome allow virions to efficiently replicate in macrophages and monocytes, ultimately resulting in FIPV [11]. Detection of FCoV S gene mutations is considered as a tool to diagnose FIPV [12,13]. FIP is typically characterized by a fibrinous and granulomatous serositis, protein-rich serous effusions, and pyogranulomatous lesions in several organs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…At present, TaqMan based real-time PCR and conventional PCR assays for detecting FCoV have been previously reported [12][13][14]. However, conventional PCR methods are not quantitative and can sometimes include non-specific products of the same size.…”
Section: Discussionmentioning
confidence: 99%